Genetic diversity and evidence of recent demographic expansion in waterbird populations from the Brazilian Pantanal - Lopes,IF. (2007)
The present study determined nuclear and mitochondrial (mtDNA) levels of genetic variability and phylogeographic patterns in breeding populations of Roseate Spoonbill (N = 57), Wood Stork (N = 89), and Jabiru Stork (N = 30), sampled in the Brazilian Pantanal. These species were selected since they are bioindicators of wetlands health and are threatened in other parts of their distribution. As they are in close association with this ecosystem, they are appropriate for studying the effects of Pleistocene climatic changes on their demographic patterns. Levels of nuclear genetic diversity in Pantanal populations were not significantly different from those of other populations throughout the American continent, where they are considered threatened or of special concern. Reduced levels of mtDNA genetic diversity were observed in the Central American population of Jabiru Stork in comparison to the Pantanal population. Recent demographic expansion in the Pantanal was markedly evidenced by unimodal patterns of mismatch distribution and Fus Fs neutrality test in these three species. We hypothesize that the average time of population expansion (between 30,843 and 14,233 years before present) is associated to responses of these birds populations to paleoclimatic changes in these wetlands during the last glaciation period. We recommend special conservation efforts with the Jabiru Stork populations, a genetic monitoring program based on mtDNA, and an ecological characterization of these waterbirds species throughout their distribution range.